The German shipbuilding industry in the world market - Werner Fante (Intereconomics, 1975)
The following article outlines the position of the German shipubilding industry in the world market against the background of the changes in demand which followed upon the mineral oil crisis. Emphasis is laid on the adverse effects of competition-distorting measures, and suggestions are made for their removal.
Keywords: 330; Shipbuilding